Mechanistic Approach for Reducing the Thickness of Asphalt Layer Incorporating Steel Slag Aggregate - Adham Mohammed Alnadish; Yusri Mohamad Aman (Salehan Institute of Higher Education, 2018)
This study aimed to evaluate the possibility of reducing the thickness of asphalt layer as a novel solution for the high density of asphalt layer incorporated with steel slag aggregate, which increase the cost of transportation. Mechanistic-Empirical Pavement Design (MEPDG) approach was employed to evaluate the benefits of introducing polyvinyl alcohol fiber in terms of reducing the thickness of asphalt layer as well as the extension service life of asphalt layer. On the other hand, the correlation between creep strain slope (CSS) and secant creep stiffness modulus (SCSM) were assessed to provide a better evaluation and understanding concerning of the outputs of the dynamic creep test. The findings of this study showed that introducing polyvinyl alcohol fiber into the mixtures at the optimum content (0.5 kg/ton) have reduced the thickness of asphalt layer by approximately 10%. Additionally, polyvinyl alcohol fiber has increased the performance of the asphalt mixtures concerning of resilient modulus and dynamic creep. Furthermore, the correlation between CSS and SCSM was strong, which indicates that evaluation of permanent deformation using CSS and SCSM parameters provides better actual assessment than accumulation strain.